2002
DOI: 10.1055/s-2002-20606
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance hydrometry: non-invasive quantification of the exocrine pancreatic function

Abstract: Our study demonstrated the feasibility of measuring pancreatic output by MRH after stimulation with secretin. Moreover, a distinction between normal secretion and patients with chronic pancreatitis is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Under secretin stimulation, the increase of the pancreatic exocrine volumes over time was linear for all subjects, followed by a plateau phase in 30% of the examinations in the control group, in 15% in patients with impaired pancreatic exocrine function and in 70% in patients with preserved pancreatic exocrine function. According to our results, the observation of a plateau phase at the end of the experiment does not correlate to a reduced secretory capacity of the exocrine pancreas [17]. Rather, it may correlate to the achievement of the maximal excretory capacity before the end of the acquisition.…”
Section: Before Treatmentcontrasting
confidence: 60%
See 4 more Smart Citations
“…Under secretin stimulation, the increase of the pancreatic exocrine volumes over time was linear for all subjects, followed by a plateau phase in 30% of the examinations in the control group, in 15% in patients with impaired pancreatic exocrine function and in 70% in patients with preserved pancreatic exocrine function. According to our results, the observation of a plateau phase at the end of the experiment does not correlate to a reduced secretory capacity of the exocrine pancreas [17]. Rather, it may correlate to the achievement of the maximal excretory capacity before the end of the acquisition.…”
Section: Before Treatmentcontrasting
confidence: 60%
“…Previous studies have suggested the great potential of S-MRCP in such an attempt [11,12,[15][16][17]. The present study has demonstrated that S-MRCP allows quantification of pancreatic exocrine secretions during secretin stimulation and, although these initials results were obtained in a limited number of patients, suggests that it Numbers correspond to patients in Table 1 Fig .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations